2009
DOI: 10.1007/s10897-009-9234-z
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Genetics Service Providers’ Practicing in a Culturally and Linguistically Diverse Population: An Australian Experience

Abstract: This paper explores the perceived challenges facing clinical genetics practitioners in multicultural Australia. Focus groups conducted with 53 practitioners explored: 1) participants' experiences and definitions of cultural diversity; 2) their use of educational resources with clients; 3) their experiences with culturally diverse groups/individuals in practice; 4) their experiences working with interpreters; and 5) the impact culturally specific educational training and/or experiential learning had on their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Single mothers more frequently experience financial hardship, physical and mental health problems and difficulties in caring for their children, which may explain this finding . Our finding that mothers with English as a second language reported lower costs of HS for their depressive symptoms supports evidence of language‐based and culture‐based barriers to access in Australian community health care . Finally, maternal completion of high school was associated with higher HS costs for infant's behaviour problems and to some extent maternal depressive symptoms, in line with Steele et al .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Single mothers more frequently experience financial hardship, physical and mental health problems and difficulties in caring for their children, which may explain this finding . Our finding that mothers with English as a second language reported lower costs of HS for their depressive symptoms supports evidence of language‐based and culture‐based barriers to access in Australian community health care . Finally, maternal completion of high school was associated with higher HS costs for infant's behaviour problems and to some extent maternal depressive symptoms, in line with Steele et al .…”
Section: Discussionsupporting
confidence: 88%
“…31,34 Our finding that mothers with English as a second language reported lower costs of HS for their depressive symptoms supports evidence of language-based and culture-based barriers to access in Australian community health care. 35,36 Finally, maternal completion of high school was associated with higher HS costs for infant's behaviour problems and to some extent maternal depressive symptoms, in line with Steele et al 37 who found that depressed individuals who have completed high school have a higher rate of mental HS use than those who did not complete high school.…”
Section: Discussionmentioning
confidence: 53%
“…Lessons learned : (1) If it is suspected that there is a low level of health literacy as it relates to Western medicine, attempts should be made to incorporate the family’s traditional medicine beliefs, such as curses and bad blood, into a simplified Western medicine-oriented genetic counseling approach regarding genes, patterns of inheritance, and recurrence risks (Parker et al 2003; Saleh et al 2009). (2) There may be different expectations for how much clinical information the medical and genetic staff want to provide, compared to how much the family wants to hear and understand.…”
Section: Resultsmentioning
confidence: 99%
“…Cultural variations in perceptions of which relatives constitute close family members have been identified, for example among Chinese Australians, 41 underlining how patterns of inheritance for disease may be variably understood, and consistent with the confusion about this noted here. 23 Other evidence also suggests differing kinship systems may affect the way people view inheritance, and thus genetic counselling, because of family privacy, 36, 42 or highlights cultural differences in people's advice seeking about cancer. 43 …”
Section: Discussionmentioning
confidence: 99%